SISTEM PEMANFAATAN ENERGI SURYA UNTUK PEMANAS AIR DENGAN MENGGUNAKAN KOLEKTOR PALUNGAN - Fatmawati '; Maksi Ginting; Walfred Tambunan (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted on Solar Energy Utilization System for Water Heater using Trough Collector. This research was carried out using an experimental method by putting in place an opened trough collector that exposed to sunlight. The highest temperature of collector produced was 50,03°C in average with an average temperature of water in the tank was 40,07°C at 1 PM, while the lowest temperature of collector was 39,14°C in average with an average temperature of water in the tank was 35,28°C at 10 AM. The highest temperature of collector occured at 1 PM, because the intensity of solar radiation at the time reached the maximum value. The experimental results showed that the higher the intensity of solar radiation, the higher the temperature of the water produced. The temperature of collector was also influenced by loss heat of the collector conduction. The highest loss heat by conduction was 29,05 W at 1 PM, while the lowest loss heat by conduction was 16,85 W at 10 AM.